On the center-stable manifolds for some fractional differential equations of Caputo type - Peng, Shan; Wang, JinRong; Yu, Xiulan (Nonlinear Analysis: Modelling and Control, 2018)
This paper is devoted to study the existence of center-stable manifolds for some planar fractional differential equations of Caputo type with relaxation factor. After giving some necessary estimation for Mittag–Leffler functions, some existence results for center-stable manifolds are established under the mild conditions by virtue of a suitable Lyapunov–Perron operator. Moreover, an explicit example is given to illustrate the above result. Finally, high-dimensional case is considered.